An Analysis of Contribution From Hotel and Restaurant Taxes to Manado City District Own Revenue - Anita Ludia Vivian Wauran (Future Science, 2020)
One of the efforts in financing regional development is to increase regional income sourced from regional taxes. The Manado City Government in carrying out the effort to increase the regional tax is carried out by the Regional Tax and Retribution Management Agency as a place to carry out the Regional Government's authority in the context of decentralization in the area of regional income, especially in the area of Manado's local tax. The source of revenue from District Own Search Revenue of Manado City comes from local taxes, such as hotel taxes, restaurants, entertainment, billboards, parking, water, and land taxes, swallow nests, Land and Building taxes P2, BPHTB, PLN, and Non-PLN Street lighting taxes, minerals nonmetal and rock. This research aims to find out how much the contribution of hotel and restaurant taxes can be generated as District Own Search Revenue with the growth of tourism that continues to increase coupled with the growth of hotels and restaurants in Manado City, with the benefits of the research is expected to provide input to the Manado City government in efforts to increase District Own Search Revenue through hotel and restaurant taxes. This research uses a contribution analysis, with the average contribution of hotel and restaurant tax realization to District Own Search Revenue per year of 7.06% and the level of effectiveness of hotel and restaurant taxes running fluctuations from year to year.